CONCEPT AND GENERAL CHARACTERISTICS OF MILITARY PROPERTY - Piskun, Ivan; Sokolovsky, Maksym (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: of the article is aimed at defining the essence of the concept of "military property", as well as the classification of its types, taking into account the multifaceted nature of this complex category, which combines legal, financial, economic, social and other characteristics. Research methods: the methodological basis of the research was made up of general scientific and specifically legal methods of cognition, the use of which made it possible to analyze different approaches to defining the concept of "property" at the legislative level, conceptual ideas of scientists regarding the characteristics of this category from the point of view of law and economics. In particular, the concept of "military property" was defined using the dialectical method, its main features and structure were highlighted. Results: as a result of the conducted research, a definition of military property was provided, which should be understood as immovable and movable property of general and special purpose, which belongs to the state property and is attached to the structures of the Armed Forces of Ukraine, other military formations under the right of operational management, which is used by them exclusively for functional and purposeful purpose in order to perform its functions and serve military personnel, as well as to conduct economic activities in accordance with the procedure established by the legislation of Ukraine. Discussion: in the structure of military property, it is necessary to distinguish directly military property and property, which by its nature is military only due to its attachment to units of the Armed Forces of Ukraine. This indicates the need to systematize and organize the types of military property, which can be classified according to its purpose into two large groups: general purpose military property and special purpose military property. The issue of the composition of military property requires further scientific development, the solution of which is important for determining the necessary mechanisms for legal regulation of relations regarding the possession, use and disposal of military property.